Colouterine and Jejunouterine Fistula Secondary to Chronic Diverticulitis - Ilias Galanis; Georgios Floros; Christophoros Theodoropoulos; Myriam Metaxa; Panagiotis Theodoropoulos; Panagiotis Tsintavis; Dimitrios Bartziotas; Georgios Giannos; Georgios Stylianidis; Georgios Papadopoulos (Case Reports in Gastrointestinal Medicine)
Fistulae between the colon or the small intestine and the uterus are extremely rare as the uterus is a thick, muscular organ. Here, we present the case of a 74-year-old female presenting to our surgical department because of fecal vaginal discharge for the past few months, which proved to be caused by a combined colouterine and jejunouterine fistula due to chronic diverticulitis. Total abdominal hysterectomy with bilateral oophorectomy with en bloc resection of part of the jejunum and the sigmoid colon and primary anastomoses were performed. This case represents an unusual type of diverticulitis complication and aims to point out the diagnostic and therapeutic issues of such a rare medical condition.